2017
DOI: 10.1111/maec.12449
|View full text |Cite
|
Sign up to set email alerts
|

Trophic structure of mesopelagic fishes in the Gulf of Mexico revealed by gut content and stable isotope analyses

Abstract: Mesopelagic fishes represent an important component of the marine food web due to their global distributions, high abundances and ability to transport organic material throughout a large part of the water column. This study combined stable isotope (SIAs) and gut content analyses (GCAs) to characterize the trophic structure of mesopelagic fishes in the North‐Central Gulf of Mexico. Additionally, this study examined whether mesopelagic fishes utilized chemosynthetic energy from cold seeps. Specimens were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 97 publications
(227 reference statements)
4
37
1
1
Order By: Relevance
“…Similar to zooplankton, we found that some migrating mesopelagic micronekton exhibited lower δ 15 N values than those of mesopelagic nonmigrators (as in Valls et al ; McClain‐Counts et al ; Fig. ).…”
Section: Discussionsupporting
confidence: 81%
“…Similar to zooplankton, we found that some migrating mesopelagic micronekton exhibited lower δ 15 N values than those of mesopelagic nonmigrators (as in Valls et al ; McClain‐Counts et al ; Fig. ).…”
Section: Discussionsupporting
confidence: 81%
“…Herbivorous copepods and euphausiids are the mostly commonly used marine organisms (e.g. Marsh et al 2017, McClain-Counts et al 2017, thus propagating the isotopic error associated with low d 15 N Bulk values to consumer TP Bulk estimates through the food web. Finally, some maps of marine d 15 N Bulk isoscapes are modeled using zooplankton data sets (Graham et al 2010, McMahon et al 2013, with the direct potential biological outcome of erroneous interpretation of animal movements.…”
Section: Perspectivesmentioning
confidence: 99%
“…Trophic ecology of myctophid communities has been investigated through studies of gut content analyses (e.g. Clarke, 1980;Gartner, 1992, Hopkins et al, 1996;Bernal et al, 2015;McClain-Counts et al, 2017) which identified these groups of fishes as mainly zooplankton feeders. More recent studies based on bulk stable carbon (δ 13 C) and nitrogen (δ 15 N) signatures have determined the trophic levels of several species in the Tasman Sea (Flynn and Kloser, 2012), Mediterranean Sea (Fanelli et al, 2011;Valls et al, 2014), and Gulf of Mexico (McClain-Counts et al, 2017).…”
Section: Introductionmentioning
confidence: 99%